Association of cerebral palsy with Apgar score in low and normal birthweight infants: population based cohort study. (7th October 2010) - Lie, Kari Kveim; Grøholt, Else-Karin; Eskild, Anne
Abstract : Objectives To assess the association of Apgar score 5 minutes after birth with cerebral palsy in both normal weight and low birthweight children, and also the association with the cerebral palsy subdiagnoses of quadriplegia, diplegia, and hemiplegia. Design Population based cohort study. Setting The Medical Birth Registry of Norway was used to identify all babies born between 1986 and 1995. These data were linked to the Norwegian Registry of Cerebral Palsy in Children born 1986-95, which was established on the basis of discharge diagnoses at all paediatric departments in Norway. Population All singletons without malformations born in Norway during 1986-95 and who survived the first year of life (n=543 064). Main outcome measure Cerebral palsy diagnosed before the age of 5 years. Results 988 children (1.8 in 1000) were diagnosed with cerebral palsy before the age of 5 years. In total, 11% (39/369) of the children with Apgar score of less than 3 at birth were diagnosed with cerebral palsy, compared with only 0.1% (162/179 515) of the children with Apgar score of 10 (odds ratio (OR) 53, 95% CI 35 to 80 after adjustment for birth weight). In children with a birth weight of 2500 g or more, those with an Apgar score of less than 4 were much more likely to have cerebral palsy than those who had an Apgar score of more than 8 (OR 125, 95% confidence interval 91 to 170). The corresponding OR in children weighing less than 1500 g was 5 (95% CI 2 to 9). Among children with Apgar score of less than 4, 10-17% in all birthweight groups developed cerebral palsy. Low Apgar score was strongly associated with each of the three subgroups of spastic cerebral palsy, although the association was strongest for quadriplegia (adjusted OR 137 for Apgar score <4 v Apgar score >8, 95% CI 77 to 244). Conclusions Low Apgar score was strongly associated with cerebral palsy. This association was high in children with normal birth weight and modest in children with low birth weight. The strength of the association differed between subgroups of spastic cerebral palsy. Given that Apgar score is a measure of vitality shortly after birth, our findings suggest that the causes of cerebral palsy are closely linked to factors that reduce infant vitality.